Estudo experimental do comportamento mecânico de estrato Silto-Argiloso (Massapê) para fundações superficiais - Chagas, Gleiber da Silva (2014)
The design of shallow foundations requires defining clearly and objectively to the soil under study, the load capacity and the prediction of settlements that undergoes structure, based on the mechanical properties obtained from laboratory testing and field. The plaque assay is one of the safest ways to get this information from direct loading, which produces, in reduced scale, the behavior of the Future Foundation. The tests performed in this study were performed in three steps: geotechnical characterization (particle size, density determination, consistency limits, standard Proctor compaction and California bearing ratio (ISC)​​); Special laboratory tests (density and shear); and field trials (load tests). The objective of this study is to evaluate the evidence from conducting direct load with soil and flooded in natural moisture, if forecasts of potential collapse and expansion, made ​​from single and double edométricos tests are able to give consistent evidence. It was observed that results of double edometricos trials, conducted in silty clay soil of the city Ico, provided more consistent estimates for situations of soil collapse. Furthermore, the technique of compression problematic soils was adequate to mitigate or even nullify, problems related to the collapse and expansion of the studied soil.